Implementation of Medan Mayor Regulation Number 27 of 2020 Concerning the Implementation of New Habits Adaptation to Covid 19 Pandemic Conditions in Medan (Study in Tanjung Mulia Hilir Village, Medan Deli District) - Syahputra, Hendra; Lubis, Maksum Syahri; Sinaga, Rudi Salam (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aims of this is Implementation of Medan Mayor Regulation Number 27 of 2020 Concerning the Implementation of New Habits Adaptation to Covid 19 Pandemic Conditions in Medan. This study use qualitative research. The result show tha the New Habit Adaptation Policy in the Corona Virus Disease 2019 (covid 19) Pandemic Condition in Tanjung Mulia Hilir Village, Medan Deli District, is still not running optimally because there are still some people who are not obedient to government regulations. Forming crowds or crowds or gatherings so that this is an unpreparedness of the community in following the adaptation of new habits in the Tanjung Mulia Hilir Village, Medan Deli District.